Black Holes Effect on Rapid Stellar Jumps and Tidal Disruptions of Stars - Sadiq, Sabir (Transactions on Engineering and Computing Sciences, 2024)
In the present work, black hole tunnel effect on a rapid stellar jumps and tidal disruptions of stars are two important subjects in this discussion. The life cycle of stars gone slowly when stars being in distant places from a black hole, otherwise the life cycle of low mass stars and high stars are gone quickly with burning much of their fuel of fusion when such stars orbit the black hole closely. Gravity is a cosmic fabric distortion in the three dimensions under the effect of black holes, Planets, and stars. Stars and planets are tidally disrupted by celestial objects and black holes. Cosmic fabric matter is warping strongly during direct interactions between Stars and black holes. The surface temperature and luminosity of stars will increase rapidly when they orbit the black hole in much close region. The centre of star may shrink inward and its atmosphere will expand outward shown clearly like blue spikes and spicules of hot plasma on its surface after an excited star passed close to the black hole or orbits it.